2020
DOI: 10.1016/j.physletb.2020.135305
|View full text |Cite
|
Sign up to set email alerts
|

HERA data and collinearly-improved BK dynamics

Abstract: Within the framework of the dipole factorisation, we use a recent collinearly-improved version of the Balitsky-Kovchegov equation to fit the HERA data for inclusive deep inelastic scattering at small Bjorken x. The equation includes an all-order resummation of double and single transverse logarithms and running coupling corrections. Compared to similar equations previously proposed in the literature, this work makes a direct use of Bjorken x as the rapidity scale for the evolution variable. We obtain excellent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 56 publications
(178 reference statements)
3
59
0
Order By: Relevance
“…While as we have discussed there are good analytical approximations, a full analytical solution of the BK equation does not exist. Numerical simulations have, however, been known for some time for the LLx BK equation [169], the LLx+running coupling BK equation [170,171], and even more recently the full NLLx equation implementing collinear resummation [172,173]. In particular, it was shown in [173] that this NLLx framework provides very good agreement with the HERA data.…”
Section: G the State Of The Art In The Cgc Eftmentioning
confidence: 99%
“…While as we have discussed there are good analytical approximations, a full analytical solution of the BK equation does not exist. Numerical simulations have, however, been known for some time for the LLx BK equation [169], the LLx+running coupling BK equation [170,171], and even more recently the full NLLx equation implementing collinear resummation [172,173]. In particular, it was shown in [173] that this NLLx framework provides very good agreement with the HERA data.…”
Section: G the State Of The Art In The Cgc Eftmentioning
confidence: 99%
“…The studies performed in Refs. [69][70][71], which disregarded the dependence on the impact parameter, demonstrated that it is possible to obtain a good description of the inclusive HERA data by taking into account these corrections to the kernel. However, in order to describe in detail exclusive processes, it is fundamental to take into account also the impactparameter dependence of the dipole-target scattering amplitude.…”
Section: Formalismmentioning
confidence: 99%
“…The initial condition for Im S, which we derive here, depends not only on the impact parameter and the dipole vectors but also on their relative angle, and on the light-cone momentum fraction x in the target. In fact, the BK equation in its standard formulation evolves the wave function of the dipole projectile, and the evolution "time" is then related to the minus component of the momentum of the gluon in the proton target [47][48][49]. Ducloué et al have reformulated [48] BK evolution at NLO in terms of the target rapidity (or Bjorken-x).…”
mentioning
confidence: 99%
“…In fact, the BK equation in its standard formulation evolves the wave function of the dipole projectile, and the evolution "time" is then related to the minus component of the momentum of the gluon in the proton target [47][48][49]. Ducloué et al have reformulated [48] BK evolution at NLO in terms of the target rapidity (or Bjorken-x). They obtained an evolution equation which is non-local in rapidity and which depends explicitly on the gluon's plus momentum fraction x = k + g /P + .…”
mentioning
confidence: 99%